Experimental evaluation of biological regeneration of arable soil: The effects of grass-clover leys and arbuscular mycorrhizal inoculants on wheat growth, yield, and shoot pathology - Austen, Nichola; Tille, Stefanie; Berdeni, Despina; Firbank, Leslie G.; Lappage, Martin; Nelson, Michaela; Helgason, Thorunn; Marshall-Harries, Ewan; Hughes, H. Bleddyn; Summers, Richard; Cameron, Duncan D.; Leake, Jonathan R. (Frontiers in Plant Science, 2022)
UK wheat yields have plateaued over the last 25 years, during which time most arable land has been annually cropped continuously with short rotations dominated by cereals. Arable intensification has depleted soil organic matter and biology, including mycorrhizas, which are affected by tillage, herbicides and crop genotype. Here, we test whether winter wheat yields, mycorrhization, and shoot health can be improved simply by adopting less intensive tillage and adding commercial mycorrhizal inoculum to long-term arable fields, or if 3-year grass-clover leys, followed direct drilling are more effective for biological regeneration of soil with reduced N fertilizer. We report a trial of mycorrhization, ear pathology, and yield performance of the parents and four double haploid lines from the Avalon x Cadenza winter wheat population, in a long-term arable field divided into replicated treatment plots. These plots comprised wheat lines grown using ploughing or disc cultivation for 3-years, half of which received annual additions of commercial arbuscular mycorrhizal (AM) inoculum, compared to 3-year mown grass-clover ley plots treated with glyphosate and direct-drilled. All plots annually received 35 kg N ha-1 fertilizer, without fungicides. The wheat lines did not differ in mycorrhization which averaged only 34% and 40% of root length colonized (RLC) in the ploughed and disc cultivated plots respectively, and decreased with inoculation. In the ley, RLC increased to 52%. Two wheat lines were very susceptible to sooty ear mould, which was lowest in the ley, and highest with disc cultivation. AM inoculation reduced ear infection by >50% in the susceptible lines. In the ley, yields ranged from 7.2-8.3 t ha-1 achieving 92-106% of UK average wheat yield in 2018 (7.8 t ha-1), but using only 25% of average N fertilizer. Yields with ploughing and disc cultivation averaged only 3.9 and 3.4 t ha-1 respectively, with AM inoculum reducing yields from 4.3 to 3.5 t ha-1 in ploughed plots, with no effect of disc cultivation. The findings reveal multiple benefits of reintegrating legume-rich leys into arable rotations as part of a strategy to regenerate soil quality and wheat crop health, reduce dependence on nitrogen fertilizers, enhance mycorrhization, and achieve good yields.